Pythagorean Fuzzy Decision-Making Framework for Sustainability Assessment of Intercity Bus Terminals - Ayyildiz, Ertugrul; Kavus, Bahar Yalcin; Taskin, Alev (SAGE PUBLICATIONS INC, 2026)
Sustainability assessments of intercity bus terminals are increasingly important because of their environmental, social, and infrastructural impacts on urban systems. However, existing studies mainly focus on urban transport and often overlook tangible infrastructure aspects. This study addresses this gap by proposing an integrated sustainability assessment methodology tailored for intercity bus terminals, incorporating the novel Tangibles dimension alongside economic, environmental, and social pillars. A hybrid multi-criteria decision-making (MCDM) framework is developed, combining Pythagorean Fuzzy Stepwise Weight Assessment Ratio Analysis (PF-SWARA) and Pythagorean Fuzzy Technique for Order Preference by Similarity to Ideal Solution (PF-TOPSIS) to handle uncertainty and subjectivity in expert evaluations. The methodology is applied to seven intercity bus terminals in & Idot;stanbul, T & uuml;rkiye. The results reveal that safety and security-related criteria received the highest importance weights, highlighting the critical role of secure infrastructure in sustainable terminal evaluation. Sensitivity and comparative analyses confirm the robustness and adaptability of the proposed model. This study contributes a novel decision support tool for sustainable transportation infrastructure planning and offers practical guidance for terminal development policies. Future research may explore applying the model in different geographic contexts and extending the analysis with alternative distance metrics.
Keywords: environmental impact; sustainability assessment; intercity bus terminals; pollution reduction; Pythagorean fuzzy numbers; decision-making; SELECTION; Engineering; Transportation